Single Switched Non-isolated High Gain Converter - Lopamudra Mitra; Ullash Kumar Rout (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents a new single switched inductor- capacitor coupled transformer-less high gain DC-DC converter which can be used in renewable energy sources like PV, fuel cell in which the low DC output voltage is to be converted into high dc output voltage. With the varying low input voltages, the output of DC-DC converter remains same and does not change. A state space model of the converter is also presented in the paper. This constant output voltage is obtained by close loop control of converter using PID controller. High voltage gain of 10 is obtained without use of transformer. All the simulations are done in MATLAB-SIMULINK environment.